2008
DOI: 10.1098/rspb.2007.1779
|View full text |Cite
|
Sign up to set email alerts
|

On status badges and quality signals in the paper waspPolistes dominulus: body size, facial colour patterns and hierarchical rank

Abstract: To establish a dominance order, social animals often rely on indicators of fighting to avoid costly aggressive encounters. In some species, individuals use colour patterns to signal their social status. Recent studies claimed that facial markings in the eusocial paper wasp Polistes dominulus are status badges that allow co-foundresses to form a linear hierarchy based on individual quality. Here, we evaluated facial patterns in natural populations of P. dominulus, in its native range, to observe whether the mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 40 publications
5
79
1
1
Order By: Relevance
“…Tibbetts & Dale (2004) suggested that the cost of this badge is not due to pigment production, since it represents only 1% of the total body pigment, but to the social costs that it entails. In contrast, this badge of status is absent in the nesting foundresses of an Italian population (Cervo et al 2008). Furthermore, although Zanette & Field (2009) did report a correlation between facial markings and dominance in a Spanish population, this was no longer significant when other factors (e.g.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Tibbetts & Dale (2004) suggested that the cost of this badge is not due to pigment production, since it represents only 1% of the total body pigment, but to the social costs that it entails. In contrast, this badge of status is absent in the nesting foundresses of an Italian population (Cervo et al 2008). Furthermore, although Zanette & Field (2009) did report a correlation between facial markings and dominance in a Spanish population, this was no longer significant when other factors (e.g.…”
mentioning
confidence: 69%
“…In P. dominulus, a temperate wasp species, body size is a significant, although not absolute, predictor of rank in associative foundations, probably because it confers some competitive ability (Turillazzi & Pardi 1977;Reeve 1991;Cervo et al 2008;Zanette & Field 2009). In hover wasps, mainly because of the relatively aseasonal tropical environment and complete absence of caste dimorphism, the range of body size of individuals is less pronounced than in temperate Polistes wasps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pioneering experiment demonstrated that males of the stenogastrinae wasp Parischnogaster mellyi use a visual status badge during flying duels for winning a perch in aerial leks [14]. It was since found that visual communication plays a key role in the social interactions between colony members and indeed, a facial badge of status has been shown to convey information on the agonistic qualities in foundresses of the North American population of Polistes dominula and to regulate dominance hierarchies in the stenogastrinae wasp Liostenogaster vechti [10,11], but see [15,16]. Polistes fuscatus wasps are more aggressive to individuals with unfamiliar appearances landing on the nest [9] and they are able to remember the individual identity of partners after one week of interactions with several other wasps [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, in less-advanced eusocial species, morphological divergences between females are less pronounced, and the factors affecting caste differentiation are not well known (Smith et al, 2011;Murakami et al, 2009;2013;Jandt et al, 2014;Montagna et al, 2015). Nevertheless, evidence suggests that the morphological attributes, such as body size and ovarian state, can play an important role in establishment of the reproductive division of labor in independent-founding (IF) polistine wasps (Tibbetts & Dale, 2004;Tibbetts, 2006;Cervo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%